Switchable single-double frequency multi-wavelength Brillouin Raman fiber laser based on micro-air cavity misalignment - A. W., Al-Alimi; W. A., Khaleel; S. A., Sadeq; N. A., Cholan; M. H., Al-Mansoori; Ahmed, M. H. M.; M. A., Mahdi (Elsevier, 2022)
This study experimentally demonstrates a switchable single-double frequency spacing multi-wavelength Brillouin Raman fiber laser (MW-BRFL). The switching functionality was assisted by a micro air cavity (MAC) that was constructed by lateral misalignment of two cleaved fiber facets. Experimental results indicated that the frequency spacing of the generated channels could be switched via adjusting the MAC lateral misalignment. The laser performance was evaluated by fixing the peak power flatness to 1.5 dB. For Raman pump power of 800 mW, as many as 503 channels (39.72 nm bandwidth) with single frequency spacing of 0.079 nm were obtained when the lateral misalignment was set at 0 µm. On the other hand, with MAC misalignment of 25 µm, the laser produced 235 channels (37.03 nm bandwidth) with double frequency spacing of 0.158 nm. The peak power discrepancy between the odd and even channels was 20 dB, indicating high suppression of double-frequency spacing laser. In comparison to other switchable MW-BRFLs, this proposed configuration exhibited significant improvements with respect to channel bandwidth, flatness and suppression.